1997
DOI: 10.1016/s0921-4488(96)00905-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Lactobacillus casei upon the adhesion of enterotoxigenic Escherichia coli K99 to the intestinal mucosa in gnotobiotic lambs

Abstract: Observations were carried out of the interactions between Lactobacillus casei 294/89 and enterotoxigenic Escherichia cofi CCM 612 (OlOl:K99) in uivo. In gnotobiotic lambs, inoculation with enterotoxigenic E. coli (ETEC) resulted in diarrhea with a typical clinical picture and patho-anatomical findings. E. coli adhered to the mucosa of the digestive tract at counts amounting to IO5 per cm2. In these lambs, disturbances of intestinal biochemical processes became evident; proteolytic enzyme activity was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Therefore, an alternative approach to control giardia infection may result from the use of adherent, nonpathogenic lactic acid bacteria (LAB) to antagonize the attachment and proliferation of the trophozoites. There is a large body of evidence showing that LAB can modulate the intestinal mechanisms of defense against enteropathogens in "in vivo" models (4,5,17,26,28). Since orally administered probiotic bacteria can become an important part of the proximal small bowel microflora, it is possible that these bacteria modify the intestinal environment through their metabolic activity.…”
mentioning
confidence: 99%
“…Therefore, an alternative approach to control giardia infection may result from the use of adherent, nonpathogenic lactic acid bacteria (LAB) to antagonize the attachment and proliferation of the trophozoites. There is a large body of evidence showing that LAB can modulate the intestinal mechanisms of defense against enteropathogens in "in vivo" models (4,5,17,26,28). Since orally administered probiotic bacteria can become an important part of the proximal small bowel microflora, it is possible that these bacteria modify the intestinal environment through their metabolic activity.…”
mentioning
confidence: 99%
“…Researchers have shown that inflammatory bowel diseases like irritable bowel syndrome may be created or intensified by the change of intestinal flora (which includes putrefaction) (Shanahan, 2000). Intestinal microflora plays a vital role in inflammation of intestine and probiotics can cure this condition through the micro flora reformation (Bomba et al, 1997). Lactobacilli consumption has increased the IgM and IgA levels in the host body.…”
Section: Resultsmentioning
confidence: 99%
“…E-mail: JAVADI@IAUT.AC.IR traveler's diarrhea (Hilton et al, 1997). The inhibitory effect of Lactobacillus casei on the connection and adhesion of Escherichia coli O 101 : K 99 to the intestinal mucosa of lambs (devoid of microbes) has been tested (Bomba et al, 1997). Also, researches have indicated that L. casei can be colonized probably as a probiotic in the gastrointestinal tract of murine model and reduced colonization of enterotoxigenic E. coli (ETEC) (Mirnejad et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These differences between the groups persisted until the end of the investigation, although daily weight gains were similar. Another set of experimental data suggests that inoculation only by a single bacterium (L. casei) in gnotobiotic lambs (Bomba et al, 1997), as in gnotobiotic chicks (L. acidophilus) (Watkins et al, 1982), can protect against enterotoxigenic E. coli infection. Three other species (L. acidophilus, Saccharomyces boulardii, and E. coli) each are individually used (Figueiredo et al, 1996) also as probiotic strains to protect against enteropathogenic agents.…”
Section: Gnotobiotic and Gf Studies: Models And Approachesmentioning
confidence: 99%